Unmasking the Masquerader: A Delayed Diagnosis of MS and Its 4.5 Years of Implications in an Older African American Male - Deanna Dong; Joshua Carlson; Joseph Ruberwa; Thomas Snihur; Nawar Al-Obaidi; José Bustillo (Case Reports in Medicine)
Multiple sclerosis (MS) has classically been described as a disease of the young Caucasian female. While the prevalence may seem to be higher in Caucasians (CAs), recent studies suggest that the real incidence of MS may actually be higher in African Americans (AAs). Here, we discuss a nonclassical case of MS in an older African American male, prognostic factors, disease patterns in African Americans, and how a delay in diagnosis and socioeconomic factors can lead to worse outcomes. In patients that present with possible symptoms of MS, a high suspicion for MS should be entertained even in epidemiologically atypical patients to prevent delay in diagnosis and irreversible disability.